The role of perspective-taking on empowering the empathetic behavior of educators in VR-based training sessions: An experimental evaluation - Stavroulia, Kalliopi Evangelia; Lanitis, Andreas (My University, 2023)
VR-based training approaches can be used to empower the empathetic behavior of educators, raising their awareness and understanding of their learners, particularly in an era of social isolation and distancing. This paper presents research related to the use of VR as a tool for the practical training of educators aiming to empower their empathy skills through perspective-taking. Educator trainees participated in an experimental evaluation that involved exposure and interaction in a virtual classroom environment. Participants were divided into three groups; members of the first group experienced only the educator's perspective while members of the other two groups experienced both the educator's perspective and the perspective of students facing issues that may affect their academic performance and/or their integration in the school community. A thorough statistical analysis of the pre and post-experiment questionnaire responses, using ANOVA, indicated a significant impact of the VR intervention only for the two groups that experienced both the educator and student perspective. The results indicate the high added value of using VR with perspective-changing to strengthen empathetic behavior during the educator's training sessions.
Keywords: Educators; Empathy; Perspective-taking; Training; Virtual reality